Interaction of Mediterranean water lenses with Antarctic intermediate water off Northwest Africa - Machín, Francisco José; Pelegrí, Josep L. (Scientia Marina, 2016)
Mediterranean Water lenses (meddies) in the eastern North Atlantic, north of the Canary Islands, appear to often have their salty and nutrient-poor core accompanied by relatively fresh and nutrient-rich waters on top. We describe several occurrences of freshwater halos and berets for meddies sampled north of the Canary Islands—with instrumented moorings, Argo floats and oceanographic cruises—and identify the source of these fresh anomalies as diluted Antarctic Intermediate Water (AAIW). We propose that this capping takes place off Northwest Africa, as the southward-advected meddy interacts with the northward-advected AAIW. This interpretation is consistent with a simple analysis of the relevant advective-diffusive time scales associated with the passage of meddies under a layer of AAIW, and suggests that meddies may be a mechanism for AAIW export far into the North Atlantic Ocean. Los Meddies en el Atlántico Norte oriental, al norte de las Islas Canarias, a menudo parecen tener su núcleo salado y pobre en nutrientes acompañado de aguas relativamente frescas y ricas en nutrientes en la parte superior. Se describen varios casos de halos y boinas de agua dulce para meddies muestreados al norte de las Islas Canarias -con instrumentos anclados, perfiladores Argo y campañas oceanográficas- identificando así el origen de estas anomalías frescas como Agua Intermedia Antártica (AIAA) diluida. Proponemos que esta interacción se lleva a cabo en el noroeste de África, cuando el meddy advectado hacia el sur interactúa con el AIAA advectada hacia el norte. Esta interpretación es coherente con un simple análisis de las escalas de tiempo advectivo-difusivas asociadas con el paso de meddies bajo una capa de AIAA, y sugiere que los meddies pueden ser un mecanismo para exportar AIAA hacia el océano interior en el Atlántico Norte.